The Electrocardiogram Is a Poor Diagnostic Tool to Detect Left Ventricular Hypertrophy in Children: A Comparison with Echocardiographic Assessment of Left Ventricular Mass. (20th January 2015) - Bratincsák, András; Williams, Matthew; Kimata, Chieko; Perry, James C.
Abstract Objective The electrocardiogram (ECG) is used to detect left ventricular hypertrophy (LVH) in children and young adults, and it is considered an important screening tool for the most common causes of sudden cardiac arrest in the United States. However, the reliability and accuracy of the ECG in the detection of LVH are poorly understood. This study's objective was to assess the reliability and accuracy of ECG parameters predicting LVH in comparison with echocardiographic two‐dimensional left ventricular mass (2D‐LVM) assessment. Design Two hundred fifty patients met study criteria with complete 2D‐LVM measurements, temporally matched ECGs and no confounding structural heart defects. The echocardiographic diagnosis of LVH was made by 2D‐LVM z‐score > 2. The electrocardiographic diagnosis of LVH was fulfilled if specific Q, R, or S wave voltages exceeded the normal limits for the respective age groups established by the Davignon, Macfarlane and Rijnbeek datasets, or fulfilled the LVH criteria set forth by adult indices (Sokolow–Lyon, Cornell, Gubner, Romhilt–Estes). Results None of the ECG parameters showed significant correlation with 2D‐LVM z‐scores. In the detection of LVH, the most commonly used R in V6 voltages showed the following results: sensitivity 13–29%, specificity 77–96%, positive predictive value (PPV) 29–50%, and negative predictive value (NPV) 77%. The overall accuracy ranged 65–75%. The accuracy of adult indices for LVH ranged from 49% to 78%. Conclusions The ECG's prediction of LVH is unreliable with dismal sensitivity, variable specificity, poor PPV, and barely acceptable NPV. With such overall poor reliability, the use of current ECG standards in screening for LVH warrants reassessment.